Dynamic feasibility study yielding a criterion for optimal investment decisions based on a computer programme simulating the discounted nett present utilities of projects - Reinecke, Robert (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.B.A.) -- University of Stellenbosch, 1971.